An Analysis of Listening Comprehension Problems in Listening Subject Among Students in English Language Education Study Program of San Pedro University - Sene, Chamelya Vivi Crystanty (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
This study examined the listening comprehension issues that first-semester English language education program students encountered. A descriptive and qualitative methodology was used to conduct this study. Six students participated in this research during the first semester. Two sections of the questionnaire were filled out on paper. The result of the questionnaire showed that in the section listening material, 83% of them occasionally find it challenging to understand the complex grammatical structures related to English vocabulary when solving listening problems. Nonetheless, the majority of them selected